EFEK JENIS DAGING UNGGAS YANG BERBEDA TERHADAP KUALITAS ORGANOLEPTIK ABON - Navly Comilo Tiven; Marcus Veerman; Hartina Pembuain (Agrinimal Jurnal Ilmu Ternak dan Tanaman, 2019)
This study aims was to determine the effect of different types of poultry meat on organoleptics quality of abon. As much as 500 grams of breast meat from three types of poultry (Arabian chicken, Manila duck and pigeon) are made into abon. Boiled meat, torn to lenght, mixed evenly with spices then boiled until cooked. Add the coconut milk, cooked on low fire while stirred until the coconut milk dries, then fries using oil over low fire for 10-15 minutes, then drained to remove the oil. The abon is served in 3 different places, then tested organoleptic (color, aroma, texture, taste and preference) by 15 untrained panelists. The data obtained were analyzed by variance for complete randomized design. The results showed that the use of different poultry meat had a significant on color (P<0.01) and texture (P<0.05) of abon. The abon of pigeon meat tend to be brown, compared to abon of Arabic chicken and Manila ducks. The abon of Arabic chicken meat, the texture tends to be smooth, compared to the abon of Manila duck and pigeons. It can be concluded that for color, abon of pigeon meat is better, while for texture, abon of Arabic chicken meat is better.